IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE TOURIST INDUSTRY COUNTRY OF NORTH AFRICA - Tymoshchuk, O. O. (The actual problems of regional economy development, 2024)
The article examines the directions for the introduction of digital technologies in the tourism industry of North African countries, since their leisure services market lags far behind other Mediterranean countries in terms of the level of penetration of information and communication technologies. It is noted that digital technologies offer enormous potential for maximizing tourism revenues, increasing tourism demand, improving the quality of supply and facilitating communication. The latest digital technologies used in the tourism industry of leading North African countries are singled out: firstly, artificial intelligence and its application in top hotels in Morocco and Egypt takes place with the help of scanning the retina of the eye or fingerprints, which allows to improve the quality of customer service due to personalization services; secondly, the use of Big Data by North African tour operators makes it possible to inventory tourist resources, promote the development of recreation areas, and analyze tourist routes; thirdly, the use of blockchain technology allows to monitor real-time information about available rooms in various hotels in North African countries, to pay for accommodation, book travel services, and manage customer identification; fourth, the Internet of Things (IoT) is successfully applied in the tourism industry of North African countries to achieve the maximum correspondence of travel conditions to the individual preferences of travelers, which radically changes the entire tourism industry; fifthly, the use of mobile applications intended for travelers provides a wide range of functions, in particular, the purchase of airline tickets, hotel reservations, navigation in the area, provision of reference information about attractions, ratings of accommodation facilities. It has been confirmed that the expansion of digital technologies, combined with the reduction of equipment costs, have improved the reliability, compatibility and interconnection of numerous terminals and programs, which has turned them into a powerful tool that can bring benefits in promoting and strengthening the strategy and activities of the tourism industry of countries North Africa.